Implikasi Pendidikan Kritis dalam Pendidikan Islam - Ifa Afida (FALASIFA : Jurnal Studi Keislaman, 2016)
The problem of education is a very important issue and can not beseparated from the whole range of human life. most humanssaw education as a noble activity that will directhuman humanizing values. Basically Islamic educationstrongly emphasizes humanization and liberation as an educational orientation,and placing learners and educators alike as a subject inteaching and learning process. Relying on critical educational paradigm, thenEducation is expected to produce process and product educationhumanists. To that end, pedagogy pattern being used in the main patronteaching and learning process in the education system should be replaced byandragogy education pattern which opens up more opportunities for learnersto participate actively, critically, and creatively in the learning process.